2008
DOI: 10.2320/matertrans.mra2007632
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Re and Ru in the γ′ Phase of Ni Based Alloys

Abstract: The diffusion of Re and Ru in the 0 -Ni 3 Al phase has been investigated at a range of temperatures 1423-1523 K by using the pseudo-binary diffusion couples. It was found that the concentration gradient of Re appeared to promote the uphill diffusion of Al, whereas that of Ru did not promote the Al uphill diffusion. The cross interdiffusion coefficients ofD D Ni AlRe andD D Ni AlRu were independent of the matrix ordering since they were comparable qualitatively between those in the 0 -Ni 3 Al and in the -Ni pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…4. The self-diffusion coefficient of ruthenium (Ru) and renium (Re) in γ′ reported by Mabruri et al [11] is also displayed in Fig. 4 for comparison.…”
Section: Resultsmentioning
confidence: 86%
“…4. The self-diffusion coefficient of ruthenium (Ru) and renium (Re) in γ′ reported by Mabruri et al [11] is also displayed in Fig. 4 for comparison.…”
Section: Resultsmentioning
confidence: 86%
“…On the other hand, Ru exhibits comparable values both in the £ A and £ phases 15,18) which means that Ru diffuses in the £ A phase by a similar mechanism with that in the £ phase. The site occupancy of Ru in £ A phase in reported by Mabruri et al 15) Although the Ru site occupancy reported here is supported by some other authors, 2,11,1921) it is a speculation from the low and comparable activation energy values of Ru in both £ and £ A phases and further study is necessary for its verification. Figure 6 shows the variation of activation energies with the bond order of elements.…”
Section: Resultsmentioning
confidence: 91%
“…5. The intrinsic diffusion coefficient of ruthenium (Ru) and rhenium (Re) in the £ A phase reported by Mabruri et al 15) is also displayed in the figure for comparison. Mabruri used Darken-Manning equation 16,17) for the analysis of intrinsic diffusion coefficients.…”
Section: Resultsmentioning
confidence: 94%
“…Many experiments were undertaken to understand the mechanical properties, [6][7][8][9] as well as the locations and diffusion of Ta, [10][11][12] W, [13,14] and Re [15,16] in superalloys. Ta and Re atoms prefer to substitute Al sites in γ phase, while W atoms show no preference and can appear in both γ and Al sites in γ phases.…”
Section: Introductionmentioning
confidence: 99%